Functional Outcomes and Postoperative Cerebral Venous Sinus Thrombosis after Translabyrinthine Approach for Vestibular Schwannoma Resection: A Radiographic Demonstration of Anatomic Predictors - Gerges, Christina; Malloy, Patrick; Rabah, Nicholas; Defta, Dana; Duan, Yifei; Wright, Christina H.; van Keulen, Marte; Wright, James; Mowry, Sarah; Megerian, Cliff A.; Bambakidis, Nicholas (Journal of Neurological Surgery Part B: Skull Base, 2021)
Introduction While regarded as an effective surgical approach to vestibular schwannoma (VS) resection, the translabyrinthine (TL) approach is not without complications. It has been postulated that postoperative cerebral venous sinus thrombosis (pCVST) may occur as a result of injury and manipulation during surgery. Our objective was to identify radiologic, surgical, and patient-specific risk factors that may be associated with pCVST.Methods The Institutional Review Board (IRB) approval was obtained and the medical records of adult patients with VS who underwent TL craniectomy at University Hospitals Cleveland Medical Center between 2009 and 2019 were reviewed. Demographic data, radiographic measurements, and tumor characteristics were collected. Outcomes assessed included pCVST and the modified Rankin score (mRS).Results Sixty-one patients ultimately met inclusion criteria for the study. Ten patients demonstrated radiographic evidence of thrombus. Patients who developed pCVST demonstrated shorter internal auditory canal (IAC) to sinus distance (mean: 22.5 vs. 25.0 mm, p = 0.044) and significantly smaller petrous angles (mean: 26.3 vs. 32.7 degrees, p = 0.0045). Patients with good mRS scores (<3) appeared also to have higher mean petrous angles (32.5 vs. 26.8, p = 0.016). Koos' grading and tumor size, in our study, were not associated with thrombosis.Conclusion More acute petrous angle and shorter IAC to sinus distance are objective anatomic variables associated with pCVST in TL surgical approaches.
Keywords: sinus thrombosis; translabyrinthine; vestibular schwannoma; acoustic neuroma; petrous angle; internal auditory canal